2011
DOI: 10.1002/eji.201040710
|View full text |Cite
|
Sign up to set email alerts
|

Threshold levels of Flt3‐ligand are required for the generation and survival of lymphoid progenitors and B‐cell precursors

Abstract: The generation of B-cell precursors (BCP) from lymphohematopoietic progenitors (LHP) in bone marrow is dependent on signals provided by the receptor tyrosine kinase Flt3 and its ligand, . Mice deficient in FL exhibit striking reductions in LHP and BCP. Currently, the mechanism by which Flt3 regulates lymphoid lineage/B-cell development is unknown. Here, we show that haploinsufficiency of FL (FL 1/À ) reduced the numbers of LHP, common lymphoid progenitors, and pro-B cells, suggesting that FL levels set a thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 42 publications
6
34
0
Order By: Relevance
“…Similar CFDA dilution in both vehicle-and indomethacin-treated DC progenitor cells indicates that PGE 2 does not regulate DC progenitor cell proliferation; rather, its primary effects are on progenitor cell survival. In support of this hypothesis, recent studies have also shown that Flt3 signaling can regulate progenitor cell survival without affecting proliferation 47,48 PGE 2 is a lipid messenger that regulates the expression of effector genes downstream of G protein-coupled receptors. PGE 2 signaling through EP receptors is known to directly promote survival of colon cancer cells and myocardium by up-regulation of STAT3 and survivin.…”
Section: Discussionmentioning
confidence: 90%
“…Similar CFDA dilution in both vehicle-and indomethacin-treated DC progenitor cells indicates that PGE 2 does not regulate DC progenitor cell proliferation; rather, its primary effects are on progenitor cell survival. In support of this hypothesis, recent studies have also shown that Flt3 signaling can regulate progenitor cell survival without affecting proliferation 47,48 PGE 2 is a lipid messenger that regulates the expression of effector genes downstream of G protein-coupled receptors. PGE 2 signaling through EP receptors is known to directly promote survival of colon cancer cells and myocardium by up-regulation of STAT3 and survivin.…”
Section: Discussionmentioning
confidence: 90%
“…23 An early restriction in differentiation options parallels high expression of the Flt3 receptor. 19,24 Megakaryocyte and erythroid potentials markedly decline, and LSKs with high amounts of Flt3 are enriched for LMPP. 19,24 Therefore, we asked if quantitative differences in CD86 among Flt3 Hi LMPPs could predict differentiation potential.…”
Section: Cd86 ؊ Hscs Are Defective With Respect To Lymphopoiesis and mentioning
confidence: 99%
“…19,24 Megakaryocyte and erythroid potentials markedly decline, and LSKs with high amounts of Flt3 are enriched for LMPP. 19,24 Therefore, we asked if quantitative differences in CD86 among Flt3 Hi LMPPs could predict differentiation potential. The category was sorted into CD86 low and high subsets that were then placed in defined, serum-free, stromal cell-free cultures ( Figure 4B Figure 4).…”
Section: Cd86 ؊ Hscs Are Defective With Respect To Lymphopoiesis and mentioning
confidence: 99%
“…Several cytokines, including IL-7 and Flt3-ligand, drive early B-cell proliferation and differentiation in vivo ; however, IL-7 is the only cytokine supplement added to the methylcellulose media to promote CFU-PreB colony formation [3436]. Levels of IL-7Rα expressed on the cell surface of Hardy fractions A–D were not significantly different between Hspa9 +/− and Hspa9 +/+ mice as measured by flow cytometry (N=5/genotype) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that homeostatic regulation of B-cell numbers may account for in vivo compensation. IL-7 is the only supportive cytokine added to CFU-PreB media even though other cytokines such as Scf, Flt3-ligand and Cxcl12 regulate B-cell differentiation and proliferation in vivo [3436]. Relying solely on the IL-7 signaling cascade in CFU-PreB culture conditions in the absence of these other cytokines may sensitize cells to subtle alterations in IL-7 signaling caused by heterozygous Hspa9 loss.…”
Section: Discussionmentioning
confidence: 99%